Evaluasi Usability Aplikasi EDMODO dengan SUS dan Thematic Analysis - Mochammad Arief Hermawan Sutoyo; Puji Rahayu (Universitas Diponegoro, 2021)
The Covid pandemic that occurred in 2020 prompted the Indonesian government to issue policies related to distance education (PJJ), to avoid the spread of disease. This sudden appeal caused tertiary institutions and students who were not ready to be ready and accustomed to the situation. To do PJJ at X University, which is located in Jambi province, use EDMODO as an application to do PJJ. The use of EDMODO as a PJJ media has been going on for almost 2 semesters, but the effectiveness of teaching via EDMODO has not been studied for its success, so an analysis is needed related to the application of EDMODO as a PJJ application. The author uses a system usability scale to analyze the educational usability level of this application. From the calculation results, the average value of SUS is 71,2. However, there is a possibility of decreasing educational usability in this application. So, it is recommended that this application be developed again.